Effect of different water-to-powder ratios on the dimensional stability and compressive strength of mineral aggregate-based cements - Cleonice Da Silveira Tei̇xei̇ra; Beatriz Dulcinéia Mendes Souza; Lucas Da Fonseca Roberti Garci̇a1; Michelli Cássia Dos Santos; Ana Carolina Corrêa Néi̇s; Tchéli Cassel De Araújo; Eduardo Antunes Bortoluzzi̇ (Istanbul University, 2019)
Purpose The aim of this study was to evaluate the effect of different water-to-powder ratios on the dimensional stability and compressive strength of Portland cement and Mineral Trioxide Aggregate (MTA). Materials and Methods Five different volumes of distilled water (0.26; 0.28; 0.30; 0.33 and 0.35 mL) were used for every 1 g of the cements. Twelve samples (12 mm long x 6 mm in diameter) were prepared in Teflon molds. After measuring the initial length, the specimens were stored in distilled water for 24 hours or 30 days. At the end of these time intervals, the specimens were measured again, and the dimensional change was calculated. The same samples used in the previous test were submitted to compression in a universal test machine (1 mm/min-1). Results Analysis of the dimensional stability results showed no statistical difference between the cements, proportions and time intervals tested, or between their interactions. After 24 hours, MTA was more resistant than Portland cement (p<0.05). At 30 day-period, both cements had similar, and significantly higher resistance than they did at 24 hours (p<0.05). Conclusion The powder/water ratio had no influence on the dimensional stability of cements. Compressive strength of Portland cement was affected at the proportions of 0.30 and 0.35 mL/g.